Factors that influence muslims purchase intention on halal bakery products / Siti Aishah Hilmi - Hilmi, Siti Aishah (Faculty of Business and Management, 2018)
Bakery products have gained popularity in Malaysia recently. However Muslim consumers are still concerned of the safety, quality composition and the Halal concept of bakery products. They want to know the origin of the ingredient used and the way it was processed. The bakery ingredient should be tested for permissibility to meet the Halal compliance in order to improve consumer’s ability to buy halal food. Thus, this project paper aimed to examine the factors that influence Muslims purchase intention on Halal bakery products. Attitude, subjective norm, perceived behavioural control and knowledge are the factors that influence purchase intention used in this study. This study was conducted among Muslim consumers at Jalan Hang Tuah, Bandaraya Melaka by using convenience sampling. The data were analysed by using Statistical Package for the Social Science (SPSS) version 20 in order to obtain the results. Data were collected from 120 respondents through structured questionnaires and Google Forms. The results indicated that attitude, subjective norm, perceived behavioural control and knowledge has positive relationship with purchase intention. The results also showed that perceived behavioural control has the greatest impact on purchase intention. Based on these results, several recommendations have been made for JAKIM, Muslims entrepreneurs and future researchers to improve Halal bakery shops and products.